UPAYA HUKUM PERMOHONAN EKSEKUSI TERHADAP PUTUSAN NAFKAH HADHANAH (Studi Pelaksanaan Putusan Terhadap Putusan Pengadilan Agama Nomor : 0957/Pdt.G/2014/PA.MLG) - Tinuk Dwi Cahyani Cahyani; Komariah Komariah (Faculty of Law, University of Muhammadiyah Malang, 2017)
The judge's ruling on the provision of a living has to be protected from legal certainty and justice in the decision Number: 0957 / Pdt.G / 2014 / PA.Mlg if the Petitioner (Defendant) is a civil servant (PNS). Implementation of the provision of income by the Petitioner (Defendant Reconciliation) to the Respondent (Plaintiff of Reconstruction) in the decision Number: 0957 / Pdt.G / 2014 / PA.Mlg. The supporting or inhibiting factor in the provision of the provision of income by the Petitioner (Defendant) to the Respondent (Plaintiff) in Decision Number: 0957 / Pdt.G / 2014 / PA.Mlg which has permanent legal force. To know the implementation of the decision, it is necessary to do research which is a sociological juridical research, using Primary data type which is a decision Number: 0957 / Pdt.G / 2014 / PA.Mlg. Data collection using the analysis of the decision that has been legally fixed (inkracht), interviews, documentation and literature study. The study was taken from the decision of the Panel of Judges in the Religious Courts of Malang and the interviews of the Respondent / Plaintiffs of Reconstruction. in order to be a reference for readers. Meanwhile, there are still obstacles in Malang education office that can not be interviewed because it is not willing to be questioned or information on the grounds there has never been a similar case. The result of research has been done by the researcher that the Petitioner / Defendant of Reconstruction does not fulfill its obligation as it existed in the ruling Decision Number: 0957 / Pdt.G / 2014 / PA.Mlg which is the basis of judge consideration already has elements of justice for the parties because it is in accordance with the circumstances and the ability of the parties to perform their respective obligations. Applicant/Defendant Rekonpensi able to carry out its obligations as an educator as well as a Civil Servant (PNS). Since the verdict was read by the Panel of Judges who had been inkracht, the Petitioner / Defendant of the Reconstruction for three years ignored or neglected his obligations (hadhanah's living). No seizure of guarantee or sanction if Petitioner / Defendant Reconcile neglects to its obligation.